Peningkatan Sinergitas Lembaga Keuangan dengan UMKM melalui Seminar di Desa Panaikang, Kecamatan Pattalassang, Kabupaten Gowa, Sulawesi Selatan - Bintang Dani; Yacobus Efesus; Alifiyah Utami Faisal; Dhea Hildayanty; Nurfadya Zulfatulaela; A. Jihan Fitrayana; Muhammad Irfai Sohilauw (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
MSMEs are the backbone of the world's economy, and Indonesia is no exception. MSMEs are businesses that can withstand economic shocks and have often proven their reliability. However, behind these achievements, SMEs still leave many problems. One of them is access to financial institutions in transactions. The purpose of this activity is to synergize and increase understanding of financial institutions (banks and non-banks) with Micro, Small and Medium Enterprises (MSMEs) in Panaikang village, Pattalassang sub-district, Gowa district, South Sulawesi. This activity is in the form of a seminar held by Student Thematic Field Work Lectures (KKLT) Batch 45 Posko 8. By using pre and post test analysis before and after the seminar, the results show that the understanding of MSME about financial institutions has increased although not significantly. MSME need to be given further activities on strengthening financial literacy and inclusion